Composición bioquímica de la carne de Polymesoda radiata (Bivalvia: Corbiculidae) en Costa Rica - Ruiz Campos, Eleazar (1998)
Monthly changes in biochemical composition and condition index of the green clam, Polymesoda radiata were studied from August 1992 tbrough July 1993 in Bebedero river, Guanacaste, Costa Rica. This species has a continuous spawning throughout the year with maximun periods in December and April (following values are % means and standard deviations). Fresh meat was 12.53 ± 3.78 . Dry flesh compositions: 78.29 ± 2.15 proteins; 9. 52 ± 1.00 lipids; 5.78 ± 2.50 carbohydrates; and 6. 43 ± 2.10 ashes. Water 90.10 ± 2.14 (correlated with the spawning period). The condition index was 9.89 ± 2.14. Dry flesh caloric value: 4.51 ± 0.11 Kcal/g. The condition index, caloric value and carbohydrates decreased during the spawning periodo Lipids, proteins and ashes had not relationship with the spawning periodo The mean condition index was inverse correlation with the spawning periodo